GROWTH PATTERN OF MICROBIA TEMPEH YOGHURT WITH ADDITION OF COFFEE EXTRACT (Coffea sp.) - Srijuliani, Endang; Suhartatik, Nanik; Wulandari, Yustina Wuri (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2021)
Yogurt is a fermented product processed from milk using Lactobacillus bulgaricus and Streptococcus thermopillus bacteria. Tempeh is a food ingredient that is rich in nutrients. The content found in tempeh such as protein, dietary fiber content, calcium, B vitamins, and iron. This study aims to determine the growth pattern of acid-forming bacteria with the addition of coffee and see the chemical changes in the fermentation of tempeh yogurt with the addition of coffee. The research was conducted using a factorial Completely Randomized Design (CRD) consisting of 2 factors. The first factor is the type of coffee (arabica, robusta and liberica), while the second factor is the length of fermentation (8, 10, and 12 hours). This research started from making tempeh milk, making coffee extract, and making tempeh yogurt plus coffee extract. The resulting yogurt was then analyzed including: total acid-forming bacteria. Chemical analysis of protein content, total sugar content, and pH measurement using a pH meter. The results of the study were the microbial growth test in the range of 7.47-8.66 log CFU / ml. In testing the protein content, the result ranges between 6.33-8.60 %, for testing the total sugar content ranges between 10.66-16.89 % and the pH test ranges from 4.35-5.20. Thus it can be concluded that the addition of coffee extract to tempeh yogurt affects the growth of LAB, protein content, total sugar content and pH.